H Pendekatan Health Belief Model (HBM) Untuk Menganalisis Kepatuhan Pasien Diabetes Mellitus Dalam Menggunakan Insulin Di Kota Banjarmasin: Pendekatan Health Belief Model (HBM) Untuk Menganalisis Kepatuhan Pasien Diabetes Mellitus Dalam Menggunakan Insulin Di Kota Banjarmasin - Sariyasih Sariyasih; Iwan Yuwindry; Erlina Syamsu (LPPM Universitas Sari Mulia, 2022)
Background: Health Belief Model (HBM) is a theory used to understand health attitudes and behavior towards a disease, HBM consists of perceived vulnerability factors, perceived severity, perceived benefits, perceived barriers, and triggers to move. Efforts to prevent the spread of the covid-19 virus in Indonesia are carried out by establishing regulations to vaccinate covid-19, especially for the elderly who are susceptible to infection with a vaccination coverage of 70% to achieve Herd Immunity. Objectives: To determine the perception of vulnerability, perceived severity, perceived benefits, and perceived barriers in influencing the elderly's perception of receiving covid-19 vaccination in Tanah Bumbu Regency. Methods: This research is a cross sectional with the type of research used is quantitative. The sampling method was purposive sampling technique and the instrument used in the study was a questionnaire with google form. The data analysis used was Univariate, Bivariate with Chi Square, and Multivariate with logistic regression. Results: The study showed that from 120 elderly respondents in Tanah Bumbu Regency, 65.8% of the elderly stated that they would vaccinate against covid-19. The dominant factor in influencing vaccination is the perception of barriers, namely the high possibility of infection in the near future. Perceived susceptibility, severity, benefits and barriers have an influence on the acceptance of vaccination in the elderly in Tanah Bumbu. Demographic factors (age, gender, occupation, education, religion, whether or not a chronic disease was diagnosed) did not have a significant influence on the acceptance of the covid-19 vaccine in Tanah Bumbu Regency. Conclusion: 65.8% of the elderly in Tanah Bumbu stated that they would vaccinate against covid-19. Perceptions of barriers, benefits, vulnerabilities, severity, and triggers to move have an influence on acceptance of the covid-19 vaccination.